The way of Husband Involvement during Birth Preparedness and Complication Readiness Plan, Arba Minch town, Gamo zone, Southern Ethiopia: Qualitative Study - Tilahun Nigusie; Negussie Boti; Sultan Hussen; Bilcha Oumer (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2020)
Background: Birth-preparedness and complication-readiness is the process of planning for normal birth and anticipating the actions needed in case of an emergency. The involvement of husband during pregnancy and its complication helps an expectant mother to make timely decisions to avoid delays: The present study aim was to explore ways how husband can involve in birth preparedness and complication readiness plan, among husband living in Arba Minch Town. Materials: Qualitative study was conducted among purposely selected husbands. The data was collected using focus group discussion. A progressive approach was used to analyze the data as Miles and Huberman suggested. All focus group discussions were recorded, translated, and transcribed verbatim. An inductive approach was used in coding the substantive themes. Results: In this study, birth and complication of pregnancy were identified by most of the participants as a condition which necessitates preparedness and readiness. Participants mentioned that they had been involved in their wives birth preparedness and complication-readiness plan through: identifying place of delivery, arranging skilled birth assistance, identifying signs of labor, well understanding the date of birth, arranging cultural food, clean clothes and other materials for the baby and mother, personally accompanying, having awareness of an emergency and it's immediate action, saving for emergencies and identifying decision-maker for emergencies. Conclusions: The findings of this study revealed that creating husbands awareness focusing on their role during pregnancy will help the women to prepare early for birth and complications this will reduce the delay in deciding to seek care. The women will give birth in health faculties this will play a vital role in reducing maternal and neonatal mortality by early recognition pregnancy-related problem and by giving appropriate care for women.